Underwater spirits and sacred places: artesian springs in southwestern Missouri. (2nd October 2019) - McMillan, R. Bruce
Abstract : Indigenous people throughout Native America often bestowed special meaning and veneration upon certain landscape features. This is the case for a series of artesian springs in the upper Osage River basin in western Missouri. Artifacts and features recorded at four springs near the confluence of the Pomme de Terre and Osage Rivers indicate that particular activities were conducted around these artesian spring conduits, actions that suggest that the springs held special meaning to the aboriginal inhabitants. The purpose of this paper is to describe the phenomena observed at the springs and to offer an explanation as to the potential meaning of the artifacts and features found associated with the spring deposits.